Impact of development aid on infant mortality: Micro-level evidence from Côte d'Ivoire - Didier Wayoro; Léonce Ndikumana (University of Massachusetts, Department of Economics, 2019)
The empirical literature has failed to reach consensus on the impact of aid on development outcomes based on aggregate cross-country analysis. This study follows the current trend in the literature on the effectiveness of aid to examine the impact of local-level aid on health outcomes. We combine data on World Bank's geo-located aid projects with three rounds of Demographic Health Surveys from Côte d'Ivoire and use difference-in-difference estimation techniques to explore the effects of aid on infant mortality. We find that proximity to development aid projects is associated with reduced infant mortality. Our results are robust to mother fixed-effects estimations as well as water and sanitation projects. The evidence suggests that access to prenatal and postnatal health care are possible mechanisms through which aid may affect infant mortality.
Keywords: F35; I15; O55; 330; Aid; infant mortality; Côte d'Ivoire